Response assessment of GBM during immunotherapy by delayed contrast treatment response assessment maps - Cuccarini, Valeria; Savoldi, Filippo; Mardor, Yael; Last, David; Pellegatta, Serena; Mazzi, Federica; Bruzzone, Maria Grazia; Anghileri, Elena; Pollo, Bianca; Maddaloni, Luisa; Russo, Camilla; Bocchi, Elisa; et al. (Frontiers in Neurology, 2024)
Assessing the treatment response of glioblastoma multiforme during immunotherapy (IT) is an open issue. Treatment response assessment maps (TRAMs) might help distinguish true tumor progression (TTP) and pseudoprogression (PsP) in this setting. We recruited 16 naïve glioblastoma patients enrolled in a phase II trial consisting in Stupp protocol (a standardized treatment for glioblastoma involving combined radiotherapy and chemotherapy with temozolomide, followed by adjuvant temozolomide) plus IT with dendritic cells. Patients were followed-up till progression or death; seven underwent second surgery for suspect progression. Clinical, immunological, MRI data were collected from all patients and histology in case of second surgery. Patients were classified in responders (Progression-Free Survival, PFS>12 months) and non-responders (PFS≤12), HIGH-NK (natural killer cells, i.e. immunological responders) and LOW-NK (immunological non-responders) based on immune cells count in peripheral blood TRAMs differentiate contrast-enhancing lesions with different wash-out dynamics into hypothesized tumoral (conventionally blue-colored) vs treatment-related (red-colored). Using Receiver Operating Characteristic (ROC) curves, a threshold of -0.066 in VBlue/VCE (Volume of the blue portion of tumoral area/Volume of contrast enhancement) variation between values obtained in the MRI performed before PsP/TTP and at TTP/PSP allowed to discriminate TTP from PsP with a sensitivity of 71.4% and a specificity of 100%. Among HIGH-NK patients, at month 6 there was a significant reduction compared to baseline and month 2 in median “blue” volumes. In conclusion, in our pilot study TRAMs support the discrimination between tumoral and treatment-related enhancing features in immunological responders vs non-responders, the distinction between PsP and TTP, and might provide surrogate markers of immunological response.